Pijat Bayi untuk Merangsang Tumbung Kembang - Ade Lina, Sri; Isfaizah; Soendari (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2024)
The problem of growth and development of toddlers during the 5th year of life is a serious problem for both developed and developing countries. Factors related to children's growth and development, namely adequate nutrition, a supportive family environment are the basis for children's growth and development. Apart from that, from a personal perspective, children can be given stimulation. One form of stimulation commonly used by parents for babies is tactile stimulation in the form of baby massage. Massage is a good, useful and healthy therapy for your baby. Apart from strengthening the bond between parent and child, baby massage also helps the child's growth and development to be better. The aim of this activity is to introduce baby massage as a solution to stimulate optimal growth and development. Community Service will be carried out in 3 stages, namely the First Stage, making preparations by collaborating with partners. The second stage of implementation, before counseling is carried out, a pretest is carried out to explore the mother's knowledge regarding baby massage. Next, baby massage education and training was carried out by practicing baby massage directly on the phantom. The third stage is to carry out an evaluation by giving a posttest and direct interviews and ending by making an activity report. From the results of community service, it was found that this activity was attended by 20 mothers who had children aged 0-59 months. Before the counseling was carried out regarding baby massage, it was found that the majority of mothers' knowledge was in the poor category, namely 12 people (60%) and after the counseling was carried out, 20 people (100%) had knowledge in the good category. It can be concluded that there was an increase in knowledge before and after counseling regarding baby massage. It is hoped that parents can provide baby massage stimulation so that it will achieve optimal growth and development.   Abstrak Permasalahan pertumbuhan dan perkembangan balita pada masa 5 tahun kehidupan merupakan masalah serius bagi Negara maju ataupun Negara berkembang. Faktor yang berhubungan dengan tumbuh kembang anak yaitu nutrisi yang tercukupi, lingkungan keluarga yang mendukung merupakan dasar untuk tumbuh kembang anak. Selain itu dari segi personal anak dapat diberikan stimulasi, salah satu bentuk stimulasi yang umum dilakukan orang tua untuk bayi adalah stimulasi taktil dalam bentuk pijat bayi. Pijat merupakan salah satu terapi yang baik, bermanfaat, dan menyehatkan bagi bayi anda, selain mempererat ikatan antara orangtua dengan anak, pijat bayi pun membantu tumbuh kembang anak menjadi lebih baik. Tujuan kegiatan ini adalah memperkenalkan tentang pijat bayi sebagai Solusi untuk merangsang tumbung kembang yang optimal. Pengabdian Masyarakat akan dilaksanakan dalam 3 tahap yaitu Tahap Pertama melakukan persiapan dengan cara melakukan kerja sama dengan mitra. Tahap Kedua tahap pelaksanaan, sebelum dilakukan penyuluhan, dilakukan pretest untuk menggali pengetahuan ibu mengenai pijat bayi. Selanjutnya dilakukan edukasi dan pelatihan pijat bayi dengan mempraktekkan langsung pijat bayi pada phantom. Tahap Ketiga Melakukan evaluasi dengan cara memberikan posttest dan wawancara secara langsung dan diakhiri dengan membuat laporan kegiatan. Dari hasil pengabdian Masyarakat didapatkan bahwa kegiatan ini diikuti oleh 20 orang ibu yang memiliki anak usia 0-59 bulan. Sebelum dilakukan penyuluhan mengenai pijat bayi didapatkan sebagian besar pengetahuan ibu dalam kategori kurang yaitu sebanyak 12 orang (60%) dan setelah dilakukan penyuluhan ibu memiliki pengetahuan dengan kategori baik sebanyak 20 orang (100)%. Hal tersebut dapat disimpulkan bahwa terjadi peningkatan pengetahuan sebelum dan sesudah dilakukan penyeluhan mengenai pijat bayi.  Diharapkan orangtua dapat memberikan stimulasi pijat bayi sehingga akan mencapai pertumbuhan dan perkembangan dengan optimal.